THEORETICAL STUDY OF THE QUALITY INDICATORS OF TWO-LAYER KNITTED FABRICS OF A NEW STRUCTURE BASED ON A MATHEMATICAL MODEL (American Journal of Technology and Applied Sciences, 2023)
In this article, the quality indicators of two-layer knitted fabrics of a new structure are theoretically studied on the basis of a mathematical model.